Assessment of two-phase heat transfer coefficient and critical heat flux correlations for cryogenic flow boiling in pipe heating experiments. (April 2019) - Mercado, Mariano; Wong, Nathaniel; Hartwig, Jason
Highlights: 41 cryogenic heated tube critical heat flux data points are gathered. 3122 cryogenic heated tube heat transfer coefficient data points gathered. 20 CHF, film, and nucleate boiling correlations were assessed. Heated-tube correlations generally deviate from cryogenic heated tube data. Heated tube disparity between data and correlations is less than disparity for quenching case. Abstract: The design and development of future cryogenic transfer systems depends on accurate correlations for modeling two-phase boiling and heat transfer at reduced temperatures in both quenching and heating configurations. The penalty for poor models translates into higher margins, increased safety factors, and an overall increase in cost. Existing correlations used in fluid/thermal design codes are based on room temperature fluids and have been shown to not accurately predict heat transfer for cryogenic fluids in the quenching configuration. This paper presents the results of a deep literature review of 40 studies conducted to gather and consolidate a database of cryogenic flow boiling data in the heating configuration. The purpose of this paper is to assess the existing correlations against the gathered experimental data. Twelve sets of cryogenic two-phase heated tube data were collected which include 872 nucleate boiling, 2250 film boiling, and 41 critical heat flux data points. The data was compared against a total of 20 heat transfer coefficient and critical heat flux correlations. As in the case of the quenching configuration, results show that existing correlations do not accurately predict cryogenic heated tube data, but the disparity between heated tube data and models is not nearly as high as in the quenching configuration.